The Effects of Reward and Punishment in Violent Video Games on Aggressive Affect, Cognition, and Behavior - Carnagey, Nicholas L.; Anderson, Craig A. (Psychological Science, 2005)
Three experiments examined the effects of rewarding and punishing violent actions in video games on later aggression-related variables. Participants played one of three versions of the same race-car video game: (a) a version in which all violence was rewarded, (b) a version in which all violence was punished, and (c) a nonviolent version. Participants were then measured for aggressive affect (Experiment 1), aggressive cognition (Experiment 2), and aggressive behavior (Experiment 3). Rewarding violent game actions increased hostile emotion, aggressive thinking, and aggressive behavior. Punishing violent actions increased hostile emotion, but did not increase aggressive thinking or aggressive behavior. Results suggest that games that reward violent actions can increase aggressive behavior by increasing aggressive thinking.